Influence of altitude exposure on brain natriuretic peptide in elite alpine skiers - de Marees, M.; Wahl, P.; Maier, W.; Stauffer, T.; Mester, J. (Abstractband der 6. Internationalen Konferenz Wissenschaft und Skisport. 14.-19. Dezember 2013, St. Christoph am Arlberg, Österreich, 2013)
The risk to develop symptoms of acute mountain sickness (AMS) rises by hypoxic exposure without acclimatization, the altitude level and the exercise intensity. All of the mentioned factors are present during an on-snow training camp performed by alpine skiing teams. For the onset of an AMS, it is postulated that a disturbed volume homeostasis and a pulmonary hypertension are two underling factors. It was demonstrated that brain natriuretic peptide (BNP) is involved in processes of maintaining normal pulmonary function and fluid management. Right ventricular stretch is the strongest factor to release BNP which is produced in the ventricle and arteries (Toshner et al. 2008). So it is of high interest, if the altitude exposure and exercise intensity performed by alpine skiing teams during on-snow training possibly induces a rise of circulating BNP values.